2003
DOI: 10.1046/j.1365-2842.2003.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

Atomic analysis and knoop hardness measurement of the cavity floor prepared by Er,Cr:YSGG laser irradiation in vitro

Abstract: In the present study, the compositional changes and knoop hardness of the cavity floor prepared by Er,Cr:YSGG laser irradiation was compared with that of the conventional bur cavity. Fifteen laser and 15 bur cavities were cross-sectioned, and subjected to atomic analysis by SEM-EDX and knoop hardness test. Statistical analyses were performed using the Mann-Whitney U-test; a value of P < 0.01 was considered significant. Surface characteristics of the prepared cavities were also investigated by light microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
2
19

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 28 publications
1
53
2
19
Order By: Relevance
“…Although some researchers have reported that the mean shear bond strength resulting from laser etching is lower than that from acid etching, 11,19,20 others have reported more favorable results with laser irradiation. 12,21,22 In the present study, we found the highest bond strength in the acid-etched group (14.85 MPa Ϯ 4.59 MPa), followed by the 2-W laser-etched group (11.14 MPa Ϯ 4.75 MPa) and the 1-W laser-etched group (9.88 MPa Ϯ 4.43 MPa).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some researchers have reported that the mean shear bond strength resulting from laser etching is lower than that from acid etching, 11,19,20 others have reported more favorable results with laser irradiation. 12,21,22 In the present study, we found the highest bond strength in the acid-etched group (14.85 MPa Ϯ 4.59 MPa), followed by the 2-W laser-etched group (11.14 MPa Ϯ 4.75 MPa) and the 1-W laser-etched group (9.88 MPa Ϯ 4.43 MPa).…”
Section: Discussionmentioning
confidence: 99%
“…To prevent bacterial growth, the water was changed weekly. 11 Sixty teeth were mounted horizontally in a self-curing acrylic resin so that at least 2 mm of the buccal enamel was exposed. The buccal enamel surfaces of the teeth were pumiced, washed for 30 seconds, and dried for 10 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…It has been studied for Class V cavity preparations and caries removal, and was shown to produce irregular, rugged, and stripped surfaces on dentin, similar to the morphological changes observed in Er: YAG laserirradiated dentin 3,4) . Compared with conventional mechanical drilling systems, laser preparation produced a cavity floor with Ca/P ratio and Knoop hardness number similar to that produced by bur cutting method 5) . In addition, Er, Cr: YSGG laser preparation was capable of causing significant reductions in Escherichia coli and Enterococcus faecalis 6) .…”
Section: Introductionmentioning
confidence: 86%
“…[10][11][12][13][14][15][16] Bazı çalıĢmalarda kumlama ve lazer uygulamalarının asit uygulanmasına alternatif olacağı görüĢü var iken, baĢka çalıĢmalarda bu görüĢün tersi iddialar ortaya atılmıĢtır. [17][18][19][20][21][22][23][24][25][26][27] Sonuç olarak, bugüne kadar yapılan farklı çalıĢmalardan ortaya çıkan ortak bir görüĢ mevcut değildir. Bu nedenle, bu çalıĢma dört farklı pürüzlendirme yönteminin ortodontik braketlerin mineye makaslama bağlanma dayanımı üzerine etkisini incelemeyi amaçlamaktadır.…”
Section: Gġrġġunclassified